Antimicrobial Activity Of Moringa Oleifera Lam., Leaf Extract, Against Selected Bacterial And Fungal Strains - B.N.DEVENDRA; N.SRINIVAS; V.S.S.L.PRASAD.TALLURI; P.SWARNA LATHA (International Journal of Pharma and Bio Sciences, 2011)
Moringa oleifera Lam (Moringaceae) is a very useful tree in tropical countries. In folklore, and ayurvedic all parts of the tree used in different healing procedures for different diseases. This plant leaves are very good nutrient supplement for mall nutrition and also used as an antibiotic. Chloroform extract of plant leaves shows antibiotic property against wide range of pathogens like Escherichia coli (MTCC 443) (ZOI=08.8±1.0mm), Pseudomonas aeruginosa (MTCC 424) (ZOI=9.5±0.5mm), Staphylococcus aureus (MTCC3160) (ZOI=6.2±0.7mm) Streptococcus pyogenes (MTCC 442) (ZOI=7.0±0.5mm). Aspergillus niger (MTCC 1781) (ZOI=7.3±0.5mm), Candida albicans (MTCC 181) (ZOI=6.2±0.5mm) along with positive controls. So this plant extracts having good healing properties without side effects when compared with synthetic antibiotics.